Trichogramma (Hymenoptera: Trichogrammatidae) Species, Egg Parasitoids of Diatraea saccharalis (Lepidoptera: Crambidae) on Sugarcane (Poales: Poaceae) in Argentina - Isas, Marcos Gerardo (2016)
The aim of this study was to identify egg parasitoids of Diatrea saccharalis F., sensu Guenée (Lepidoptera: Crambidae) in sugarcane in Tucumán, Argentina. We report a new host-parasitoid association of Trichogramma atopovirilia Oatman & Platner (Hymenoptera: Trichogrammatidae) attacking D. saccharalis and the first record of Trichogramma galloi Zucchi from Argentina. Additionally, Trichogramma pretiosum Riley was recorded in this survey.